Structural Relationships of Academic Hardiness, Competence Beliefs, Intrinsic Motivation, and Planning with Agency among High School Students - Khodadad Narenji, Hassan; Naderi, Habibollah; Shojaei, Ali Asghar (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective: The present study aimed to examine the mediating role of active planning in the relationship between human agency and competence beliefs, as well as intrinsic motivation, with the moderating effect of academic hardiness among students in Ramsar and Tonekabon counties.Methods and Materials: The statistical population of this study included all male and female students in the second stage of high school in Tonekabon and Ramsar counties (8,178 students in the 2018-2019 academic year). Considering the number of items in each questionnaire used, five students were considered per item, resulting in 144 items in this study. A final sample of 720 students was selected using stratified random sampling. The study utilized the Academic Hardiness Questionnaire by Kobasa (1979), the Academic Motivation Questionnaire by Harter (1981), the Human Agency Questionnaire by Jaskylla et al. (2016), the Active Planning Questionnaire by Quine (1990), and the Competence Beliefs Questionnaire by Harter (1982). Data were analyzed using Pearson correlation coefficients and structural equation modeling via SPSS-24 and Amos-24 software.Findings: The significance statistic between the variables of academic hardiness and human agency was 2.461, which is greater than 1.96, indicating that the relationship between academic hardiness and human agency is significant at the 95% confidence level. Additionally, the path coefficient between these two variables was 0.234, demonstrating the positive impact of academic hardiness on human agency.Conclusion: The structural relationships of academic hardiness, competence beliefs, intrinsic motivation, and planning with agency among high school students in Tonekabon and Ramsar counties have a significant role.